1997
DOI: 10.1177/000348949710600210
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Utilization of the Rat Vestibular End Organs: A Quantitative 2-Deoxyglucose Study

Abstract: The local metabolic rate of glucose utilization (LMRglc) for the rat vestibular end organs was determined with a modification of the [14C]deoxyglucose method. Data are expressed as micromoles per 100 g per minute +/- SEM. Results indicate that the LMRglc is similar within the utricle (40.3 +/- 3.2) and saccule (41.2 +/- 5.5) and significantly higher than that for the superior (20.1 +/- 2.9), posterior (25.4 +/- 2.0), or lateral canal (22.0 +/- 2.6) ampullae. These differences in LMRglc may be related to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The different responses of the two end organs, otoliths and semicircular canals, in early stages of diabetes mellitus could be related to their metabolic and vascular characteristics. In murine models, evaluation of the local metabolic rate of glucose utilisation has shown similar results for the utricle and saccule, which were significantly higher than that for the superior, posterior, or lateral canal ampulla 18 . Compared to the posterior canal ampulla, the rat utricular macula is similar with respect to neuroepithelial volume, capillary surface area and blood flow, but the capillary diameter is smaller and the capillary length is greater 19 .…”
Section: Discussionmentioning
confidence: 83%
“…The different responses of the two end organs, otoliths and semicircular canals, in early stages of diabetes mellitus could be related to their metabolic and vascular characteristics. In murine models, evaluation of the local metabolic rate of glucose utilisation has shown similar results for the utricle and saccule, which were significantly higher than that for the superior, posterior, or lateral canal ampulla 18 . Compared to the posterior canal ampulla, the rat utricular macula is similar with respect to neuroepithelial volume, capillary surface area and blood flow, but the capillary diameter is smaller and the capillary length is greater 19 .…”
Section: Discussionmentioning
confidence: 83%
“…These findings suggest that this higher linear density in posterior crista sensory cells might cause the different tolerance to ototoxic drugs. Olds and Lyon [15] concluded that the local metabolic rate of glucose utilization for the rat vestibular endorgans is similar with the utricle and saccule and significantly higher than that of for the superior, posterior, or lateral canal ampullae. Lyon and Jensen [11] asserted that blood flow to all of the vestibular endorgans from rats is similar.…”
Section: Discussionmentioning
confidence: 99%